Application Of Block Printing Technique With Waste Pallet Wood On Ready-To-Wear Clothes - Suci Widya Putri; Mochammad Sigit Ramadhan (Corak, 2022)
Block printing is a decorating technique using a block coated with dye and then pressed repeatedly along the fabric to create a pattern. Currently, the block printing technique is still poorly known and developed, especially in Indonesia, even though this technique is user friendly and the materials are abundantly available. One of them is pine pallets, which are usually used to protect products in shipping goods. This study uses a qualitative method. The data was collected from literature study, observation, and exploratory experiments, which are divided into several stages. The research results show that block printing plates made of waste pallet wood can visualize the shape of the motifs on textile materials, which are then applied to the design of ready-to-wear fashion products.